Expressing Opinion in Newspaper Discourse - Zigová, Marcela (Univerzita Pardubice, 2016)
This thesis focuses on the use of evaluative language in newspaper discourse. The theoretical part describes the language of media and its main characteristics. Furthermore, it focuses on the differences between the quality and the popular press. It also describes the functions and characteristics of newspaper discourse, news values and the evaluative language. Additionally, evaluative parameters are classified. In the practical part, findings from the theoretical part are applied to the particular newspaper reports, and the evaluative language is analysed.
Vyjadřování stanoviska autora v diskursu novinových zpráv
Keywords: novinový diskurs; hodnocení; tisk; média; jazyk; stanovisko; význam; parametr; newspaper discourse; evaluation; press; media; language; opinion; meaning; parameter